Effect of Poly(Vinyl Alcohol) Addition on the Properties of Hydrothermal Derived Calcium Phosphate Cement for Bone Filling Materials - Razali N.N.; Sopyan I.; Mel M.; Salleh H.M.; Rahman M.M.; Singh R. (Institute of Physics Publishing, 2023)
Bone; Bone cement; Calcium; Calcium phosphate; Cements; Nanotechnology; Ammonium dihydrogen phosphate; Bone filling materials; Bone-fillers; Calcium phosphate cement; Effect of addition; Liquid Phase; Poly (vinyl alcohol) (PVA); Setting time; Polyvinyl alcohols